Marina : a story about plastic and the planet - Byrd, Jesse (Paw Prints Publishing, 2023)
"After Marina throws away the plastic wrapper on her sandwich, the plastic goes on a journey to disturb a series of sea creatures before, later, washing up on a beach where Marina and her family are playing. This experience is Marina's introduction to the harmfulness of single-use plastics, lighting a spark within her to learn more and do more to help the planet"--